Contagion and Visibility: Notes on the Phenomenology of a Pandemic: Contágio e visibilidade: notas sobre a fenomenologia de uma pandemia - Caron, J.-P. (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): J.-P. Caron Title (English): Contagion and Visibility: Notes on the Phenomenology of a Pandemic Title (Portuguese): Contágio e visibilidade: notas sobre a fenomenologia de uma pandemia Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 22-30 Page Count: 9 Citation (English): J.-P. Caron, “Contagion and Visibility: Notes on the Phenomenology of a Pandemic,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 22-29. Citation (Portuguese): J.-P. Caron, “Contágio e visibilidade: notas sobre a fenomenologia de uma pandemia,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 22-29.